Formulation of Black Garlic Tea with The Addition of Ginger (Zingiber officinale), Rosella (Hibiscus sabdariffa L), and Packaging Design - Putriana, Norisca Aliza; Mardawati, Efri; Rizki Sendi, Cahyani; Maulida Rahmah, Devi; Pujianto, Totok; Marta, Herlina (Indonesian Journal of Pharmaceutics, 2024)
Indonesia is globally recognized for its abundant biodiversity and is considered one of the most biodiverse countries in the world. Over centuries, local communities have explored the benefits of natural ingredients such as garlic to be used as herbal medicine. Although garlic has numerous health benefits, raw consumption is still uncommon due to its strong aroma and taste. To address this issue, black garlic, a derived product from garlic, has been developed to minimize its strong characteristics. Therefore, this research aimed to investigate formulation of black garlic tea with the addition of ginger and rosella flowers in terms of bioactive components, including total phenolic content, total flavonoid content, antioxidant activity, and organoleptic characteristics of taste and aroma. The method used involved the extraction of 12 samples. The results indicated that the highest phenolic content was 16.708 ± 0.0356 mg GAE/g with formulation of black garlic, rosella, and ginger at a ratio of 1 g: 3 g: 2 g. The highest flavonoid content was observed in formulation of black garlic, rosella, and ginger at a ratio of 2 g: 3 g: 2 g, which amounted to 13.560 ± 0.536 mg QE/g. Furthermore, formulation with black garlic, rosella, and ginger at a ratio of 2 g: 3 g: 2 g exhibited the highest antioxidant activity of 63.21%. These results showed that formulation of black garlic tea with the addition of ginger and rosella flowers could enhance the levels of bioactive components, including total phenolic content, total flavonoid content, and antioxidant activity.